PROSPEK PUPUK ORGANIK UNTUK BUDIDAYA BAWANG MERAH DI DESA KUPU, WANASARI, BREBES - Sribiyanto, Bowo; Rajiman, Rajiman; Tri Wibowo, Haris (Journal of Agribusiness and Community Development (AGRIVASI) UMUS, 2023)
This study aims to determine the prospects for the use of organic fertilizers in the cultivation of shallot bulb seeds in the Sumber Pangan farmer group, Butterfly Village, Wanasari District, Brebes Regency. The research method used is a survey with a questionnaire. The sampling technique used was the population sampling technique, namely from the entire population of 48 respondents taken by census. Data analysis used descriptive analysis using a Likert scale tool. The results showed that the prospects for using organic fertilizers were classified as good with the parameters measured being in the medium category, as evidenced by the results of the parameters measured starting from the achievement of the level of development in the high category, the ease of obtaining organic fertilizers and organic raw materials in the high category. Understanding of the function and dosage of organic fertilizers in the moderate category. Achievement of the level of use of organic fertilizers, in the medium category, achievement of the use of liquid organic fertilizers, all in the medium category. The use of solid organic fertilizers in the low category. The application of organic fertilizers is still in the low category. From the results of this study, the empowerment strategy for the Sumber Pangan farmer group is counseling with material on the manufacture and use of organic fertilizers. The development strategy is by increasing counseling to increase farmers' knowledge of attitudes and skills (PSK) regarding organic fertilizers, and attempted with demonstration plots on the use of organic fertilizers.